Pengaruh Literasi Keuangan Terhadap Keputusan Investasi Mahasiswa STIE Indragiri Rengat - Gita Sari Gustika; Hasanah Yaspita (Universitas Batanghari, 2021)
Investment is a form of investment or capital to generate wealth, which will be able to provide returns, both present and future. Not a few people still do not understand how to invest properly and correctly, so many of them are deceived by investments by offering unreasonable interest returns and unclear investment management. By using financial literacy, it can make it easier for someone to understand and know things about finance and financial risks that may occur in order to avoid financial problems. This study aims to determine the effect of financial literacy on investment decisions in society, especially students. The case study in this research is the undergraduate student of the Sekolah Tinggi IlmuEkonomi Indragiri (STIE-I) Rengat. This study uses a comparative causal quantitative approach. Based on the calculation of the sampling using purposive sampling method with the Slovin formula.Results of Simple Linear Regression Analysis, jIf financial literacy is equal to 0 (zero), the amount of investment decisions will be 8.141 points, if financial literacy increases by 1 (one) unit, investment decisions will increase by 0.506 points. And hresult of partial test (t test, obtained t count is 8,434> t table 1,985, so it can be concluded that the Financial Literacy variable (X) has an effect on the Investment Decision variable (Y).